Wyjście z ciszy. Rola kulturalna, edukacyjna i terapeutyczna Olsztyńskiej Pantomimy Głuchych - Sokołowski , Marek (Studia Edukacyjne, 2020)
The article recalls the role played by the Olsztyn Mime Ensamble in the culture of the region of Warmia and Mazury and Poland. The Ensamble gained their artistic rank thanks to the theater director, professor Bohdan Głuszczak (1936-2016).